PERAN GURU DALAM MENERAPKAN STRATEGI PEMBELAJARAN BERDIFERENSIASI PADA SEKOLAH INKLUSI - Kriza, Yossefa; Sudarti, Sudarti; Diana, Diana (Jurnal Administrasi Pendidikan Indonesia, 2024)
The population of children with disabilities in Indonesia reaches 1.6 million children, so appropriate learning activities are needed for children with disabilities in Indonesia. This study aims to identify the differentiated strategies teachers use in the learning process, the roles they play in creating an inclusive learning atmosphere, and the supporting and inhibiting factors that influence their effectiveness. This study uses a descriptive, qualitative approach. The research method used to examine natural object conditions involves triangulation (combined), inductive data analysis, and qualitative research results that emphasise meaning rather than generalisation. Data collection methods use observation, interviews and documentation. Data validity-checking techniques include source triangulation, technical triangulation, and time triangulation. The study's results indicate that teachers play a central role in creating a learning environment that is fair, adaptable, and responsive to each student's needs. This study found that teachers act as learning designers, adjusting learning materials, processes, and products to students' abilities, interests, and learning profiles, including both regular and special needs students. The implications of this research also highlight the need for closer collaboration among class teachers, special assistant teachers, and parents to identify students' learning needs, thereby making the learning process more meaningful and effective